More about branes on a general magnetized torus - De Angelis, L; Marotta, R; Pezzella, F; Troise, R (2012)
In the framework of low-energy effective actions of branes compactified on magnetized extra-dimensions, Yukawa couplings are determined for the chiral matter described by open strings attached to D9 branes having different oblique magnetization and living on a general torus T 6 with an arbitrary complex structure. These results generalize the ones already existing in literature. © 2012 SISSA.